Industry-Academia Research Collaboration; characterising structure, process & attitudes in support of best practice - Butcher, Juliette (Cranfield University, 2005)
Industry-academia collaborative research has become a subject of increasing interest in recent years to academics, industrialists and policymakers due to greater awareness of the importance of such links for innovation and the knowledge-based economy. However, such collaborations are not always successful for reasons which are poorly researched. The main objective of this thesis is to identify the main factors that impede or enhance successful research collaboration. The research agenda is guided by a review of the current literature which indicates that the effectiveness of industry-academia collaborative research depends to some extent on the following factors: (i) the motivations/objectives for collaborative research, (ii) the modes of communication between collaborative partners, and (iii) the management of the collaborative process. The influence of each of these three factors on collaboration effectiveness is investigated using a conceptual model and two pieces of complementary fieldwork. The conceptual model illustrates the relationship between the three factors and the structure of collaboration, the collaborative process and the attitudes of collaborative participants. The fieldwork activities, which provide data on individual perceptions of industry-academia collaborative research experience, comprise an interview survey of collaborative research facilitators, and a questionnaire survey of students working on projects jointly supervised by academics and industrialists. Findings from these two activities are analysed in terms of their contribution to the existing literature on industry-academia collaboration and their conformity with the conceptual model. The perspectives of the research facilitators are also directly compared with those of the students. The results support current awareness in the literature that industry-academia collaborations are difficult to analyse and manage because of their diverse structures, their dynamic nature and the variety of factors that influence their effectiveness. Whilst the research findings do provide some indication of why collaborations succeed or fail and how they can best be managed, the fact that no two collaborations are the same in terms of motivations, objectives, structure, process, outcomes, type of participants, etc., precludes prescriptive generalisations. Suggestions for best practice include adopting an adaptable management structure and using a 'relationship management' approach for long term collaborative relationships.